ค่าความเสี่ยงสำหรับการลงทุนในสัญญาซื้อขายทองคำล่วงหน้าของบริษัทประกันภัย - พิสิทธิ์ เลิศวิชญะวงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
This research is analysis of the risks of investment in gold futures contracts for insurance companies in order to calculate the most appropriate risk charge. Currently, Office of Insurance Commission (OIC) has legislated Risk Based Capital (RBC) for insurance companies to maintain capital for each risk category in order to prevent the risk of unexpected situation, so that they can continue to operate. Results show that the probability distribution of the return on gold futures contract is the Log-loistic distribution with the average rate of return is positive. However, gold futures contracts are priced based on the price of gold bullion at 96.5 percent purity, which is very volatile. This research used Value at Risk (VaR) which can be measured at the highest level of loss for each significance level in the contract and the portfolio strategy or risk tolerance. The risk charge varies according to the allocation of investment. Summary the risk charge for assessment in order to calculate the risk capital charge is 6 to 14 percent.